2002
DOI: 10.1177/014107680209500607
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Subdural Haematoma in the Elderly—A North Wales Experience

Abstract: Chronic subdural haematoma (CSDH) is predominantly a disease of the elderly. Most of the existing data come from studies done several decades ago. We examined the incidence, risk factors, clinical presentation, management and outcome in elderly patients with CSDH by retrospective study of the period 1996-1999 in the three district hospitals of North Wales. 40 cases of CSDH were identified in patients >65 years, the incidence in this population being 8.2/100,000. Falls (57%) and antithrombotic therapy (33%) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
1
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 7 publications
4
95
1
9
Order By: Relevance
“…The 30-day mortality of SDH in this population was 39%. The incidence rate for SDH in dialysis patients was 191 per 100,000 dialysis patients per year in 2002 as compared with three to 58 cases per 100,000 general population per year, reported from other studies worldwide (2)(3)(4)(5) (Figure 1).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The 30-day mortality of SDH in this population was 39%. The incidence rate for SDH in dialysis patients was 191 per 100,000 dialysis patients per year in 2002 as compared with three to 58 cases per 100,000 general population per year, reported from other studies worldwide (2)(3)(4)(5) (Figure 1).…”
Section: Resultsmentioning
confidence: 73%
“…Age has been reported in previous studies to be an independent risk factor for SDH (2-6). The incidence rate of SDH has been reported to be 3.4 per 100,000 general population per year for Ͻ65 years and a varying rate ranging from 8 to 58 per 100,000 per year in those Ͼ65 years of age (2)(3)(4). Even if all new dialysis patients were older than 65 years, the incidence rate of 200 per 100,000 of SDH in the dialysis population would still be well over that reported for the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Similar likelihoods of return to functional baseline and nonsignificant differences in the rate and risk of mortality were unexpected, as past studies have demonstrated worse outcomes and higher mortality rates following neurotrauma in older patients than in younger patients. 3,12,13 Our findings suggest that advancements in the management of intracranial hematomas, particularly postoperative ICU care and rehabilitation, may mitigate the increased risk of death traditionally associated with older age in past studies. There is some literature that has supported these findings.…”
Section: Discussionmentioning
confidence: 74%
“…The reasons why this type of hematoma occurs frequently among the elderly include an increase in antithrombotic medications, venous fragility, augmentation of the subdural space, and an increased exposure to traumatic injury resulting from frequent falls 1) . For the initial management of CSDH, numerous surgical treatments have been proposed 5,14,15,18,21) .…”
Section: Introductionmentioning
confidence: 99%